Comparison study on ship resistance among monohull, catamaran and semi-swath - Ahmad Shah Heermie Abu Bakar, 1986-; Agoes Priyanto, supervisor; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2009